Extracorporeal shockwave therapy for the treatment of knee osteoarthritis: A retrospective study. Issue 27 (July 2018) - Li, Wei; Pan, Yu; Yang, Qi; Guo, Zheng-gui; Yue, Qi; Meng, Qing-Gang
Abstract : Abstract: This retrospective study investigated the effect and safety of extracorporeal shockwave therapy (ESWT) for treatment of knee osteoarthritis (KOA). In this retrospective study, 105 patients with KOA were included. Of those, 60 patients underwent ESWT, whereas 45 patients received laser therapy. Effect was measured by the Numeric Rating Scale (NRS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). In addition, adverse events (AEs) were also recorded in this study. All outcome measurements were evaluated at the end of weeks 1, 6, and 12. Compared with the laser therapy, ESWT showed greater effect in KOA symptoms relief with regard to NRS, WOMAC total, and its subscores at week 6 ( P  < .05) and week 12 ( P  < .01) after treatment. No AE, however, occurred in both groups. The results of this retrospective study found that ESWT may be efficacious and safe for the treatment of patients with KOA. It, however, had an intrinsic limitation as a retrospective study. Prospective study with larger sample size is still needed to warrant the result of this study in the future.